A paperless laboratory facility management system - Zhang, Chao (2016)
In this project, a web-based paperless laboratory facility management system is built by following an incremental development strategy. The system is able to provide more efficient services for laboratory management and cast off paper-based works for laboratory technicians. It is able to handle facility booking and visiting requests from researchers while providing facility management and data visualization services to technicians for laboratory management. A monthly report is generated for the technicians to visualize statistics of the facility usage, user composition, as well as system incomes. This paperless laboratory facility management system has the potential to be further generalized to all laboratories with similar requirements.